Recurrence of anti-factor H associated C3 glomerulonephritis in the kidney allograft - Magriço,Rita (2017)
C3 glomerulonephritis is a rare disease defined by deposits of C3 on immunofluorescence due to dysregulation of the alternative pathway of the complement cascade. We present a case of a female patient that presented with nephrotic syndrome at the age of 18 due to C3 glomerulonephritis and progressed to end-stage renal disease after 9 years. She lost the first kidney graft on the third day after transplantation due to vascular thrombosis. A second kidney transplant was performed when the patient was 30 years old. C3 glomerulonephritis recurred on the kidney graft and the patient returned to dialysis 10 years after the transplant. Study of the alternative complement pathway revealed anti-factor H antibodies. She is currently on evaluation for a third kidney transplant and there is no consensus on the best treatment strategy. We present the literature available for treatment of C3 glomerulonephritis and the therapeutic options for this patient